An Observer's View on the Future of Asteroseismology - Paparó, Margit (Frontiers in Astronomy and Space Sciences, 2019)
Scientific research is a continuous process, and the speed of future progress can be estimated by the pace of finding explanations for previous research questions. In this observer’s based view of stellar pulsation and asteroseismology, we start with the earliest observations of variable stars and the techniques used to observe them. The earliest variable stars were large amplitude, radial pulsators but were followed by other classes of pulsating stars. As the field matured, we outline some cornerstones of research into pulsating star research with an emphasis on changes in observational techniques. Improvements from photographs, to photometry, CCDs, and space telescopes allowed researchers to separate out pulsating stars from other stars with light variations, recognize radial and nonradial pulsation courtesy of increased measurement precision, and then use nonradial pulsations to look inside the stars, which cannot be done any other way. We follow several highlighted problems to show that even with excellent space data, there still may not be quick theoretical explanations. As the result of technical changes, the structure of international organizations devoted to pulsating stars has changed, and an increasing number of conferences specialized to space missions or themes are held. Although there are still many unsolved problems, such as mode identification in non-asymptotic pulsating stars, the large amount of data with unprecedented precision provided by space missions (MOST, CoRoT, Kepler) and upcoming missions allow us to use asteroseismology to its full potential. However, the enormous flow of data will require new techniques to extract the science before the next missions. The future of asteroseismology will be successful if we learn from the past and improve with improved techniques, space missions, and a properly educated new generation.